2018
DOI: 10.1016/s0140-6736(18)31947-0
|View full text |Cite|
|
Sign up to set email alerts
|

Closed-loop insulin delivery in suboptimally controlled type 1 diabetes: a multicentre, 12-week randomised trial

Abstract: SummaryBackgroundThe achievement of glycaemic control remains challenging for patients with type 1 diabetes. We assessed the effectiveness of day-and-night hybrid closed-loop insulin delivery compared with sensor-augmented pump therapy in people with suboptimally controlled type 1 diabetes aged 6 years and older.MethodsIn this open-label, multicentre, multinational, single-period, parallel randomised controlled trial, participants were recruited from diabetes outpatient clinics at four hospitals in the UK and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
240
3
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 338 publications
(261 citation statements)
references
References 21 publications
11
240
3
7
Order By: Relevance
“…79 However, a more recent publication from the same group did not show improvements in GV measures with CoV. 80 Similarly, short-term dual-hormone studies have also reported improvements in GV. 85,86 16 | ADJUVANT THERAPY In T1DM, insulin is an essential therapy but, as described, replacement of insulin is a complex intervention with a fine balance among hypoand hyperglycaemia, poor achievement of HbA1c targets and high levels of GV.…”
Section: Continuous Subcutaneous Insulin Infusionmentioning
confidence: 97%
See 2 more Smart Citations
“…79 However, a more recent publication from the same group did not show improvements in GV measures with CoV. 80 Similarly, short-term dual-hormone studies have also reported improvements in GV. 85,86 16 | ADJUVANT THERAPY In T1DM, insulin is an essential therapy but, as described, replacement of insulin is a complex intervention with a fine balance among hypoand hyperglycaemia, poor achievement of HbA1c targets and high levels of GV.…”
Section: Continuous Subcutaneous Insulin Infusionmentioning
confidence: 97%
“…78 Closed-loop systems, also called artificial pancreas or automated insulin delivery systems, involve control algorithms that modulate insulin delivery, aiming for near-normal glucose levels while minimizing/improving hypo-and hyperglycaemia. 79,80 While most closed-loop studies have evaluated single hormone insulin-only systems, dual-hormone or bi-hormone systems that deliver both insulin and another hormone, such as glucagon or pramlintide, have also been tested. Because of the delay in onset of action of subcutaneously administered rapid-acting insulin, most closed-loop systems require a hybrid approach, characterized by manual administration of prandial boluses, ideally at 15-20 minutes pre-meal.…”
Section: Continuous Subcutaneous Insulin Infusionmentioning
confidence: 99%
See 1 more Smart Citation
“…pizza) because of the perceived ability of the closed-loop to deal with errors in carbohydrate counting and automatically address small fluctuations in blood glucose resulting from snacking or delayed absorption of fatty foods. While, in the main trial from which our participants were recruited, weight change was not significantly different between the two arms, a 2.2 kg weight gain was observed in the closed arm (as compared with 1.4 kg in the control arm) [21]. In another 3-month trial of a hybrid closed-loop delivery system, weight gains of 1.4 and 1 kg were also observed among adult and adolescent users, respectively [22].…”
Section: Discussionmentioning
confidence: 66%
“…Automatisierte Closed-Loop-Systeme, die CGM und CSII mittels eines Algorithmus verbinden, verbessern die glykämische Kontrolle, ohne das Risiko von Hypoglykämien zu erhöhen [36,37]. Zum jetzigen Zeitpunkt ist nur ein Hybrid-Closed-Loop-System in den USA und einigen europäischen Ländern auf dem Markt; dieses ist in Deutschland jedoch noch nicht verfügbar.…”
Section: Closed-loop-systemeunclassified